Documents in the history of Aboriginal education in New South Wales - Fletcher, J. J. (Carlton, N.S.W. : J. Fletcher, 1989)
Extracts from selected historical documents, 17901969, to supplement the companion volume, Clean, clad and courteous; a history of Aboriginal education in New South Wales; changing government policy, native institutions, Aborigines Protection Board, Aborigines Welfare Board, Aboriginal school system, community and race relations.
Includes index.
Available from J.J. Fletcher, 45 Bibby Street, Carlton, N.S.W. 2218.
Keywords: Aboriginal Australians -- Education -- New South Wales -- History; Education -- New South Wales -- History; Government policy - State and territory - New South Wales; Government policy - Initial period and protectionism; Race relations - Racial discrimination - Education; Government policy - Integration; Race relations - Racism - Stereotyping; Government policy - Assimilation; Education - Schools - Community relations; Education - Policy and administration; New South Wales (NSW)